1996
DOI: 10.1007/s004410050577
|View full text |Cite
|
Sign up to set email alerts
|

Electron-microscopic immunolabelling of vasoactive substances in human umbilical endothelial cells and their actions in early and late pregnancy

Abstract: Human umbilical vessels are devoid of nerves and therefore endothelial cells may play an important role in the control of feto-placental blood flow. The pharmacological effects of 5-hydroxytryptamine, histamine and endothelin were examined in umbilical arteries and veins from legal terminations (gestational age 8-17 weeks, n=12) and normal term vaginal deliveries (gestational age 38-41, n=12). Immunocytochemistry of human unbilical vessels indicated that 5-hydroxytryptamine, histamine and endothelin were local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Histamine could cause sustained vasoconstriction in all HUV in the present study, consistent with the previous non-IVF related study [ 32 ]. The maximum contractile responses to histamine in HUV were also analogous to previous study [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Histamine could cause sustained vasoconstriction in all HUV in the present study, consistent with the previous non-IVF related study [ 32 ]. The maximum contractile responses to histamine in HUV were also analogous to previous study [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…During pregnancy, HDC‐expressing mast cells were numerous in the umbilical cord and the placenta. Their location is compatible with a role for histamine in the regulation of fetal blood supply (Sexton et al, 1996). Leucocytes and inflammatory agents have also been proposed to have a regulatory role in the events leading to the parturition of the fetus (Thomson et al, 1999).…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, SP has growth-promoting actions on endothelial cells (Villablanca et al 1994), whereas adenosine, a breakdown product of ATP, stimulates retinal microvascular endothelial cell migration and tube formation (Lutty et al 1998) Human umbilical vessels are unusual in that not all the substances released during shear stress act on receptors on adjacent endothelial cells to influence local vascular tone. Histamine, 5-HT, ATP and ET, when released from umbilical endothelial cells in response to shear stress, produce local vasoconstriction (Sexton et al 1996). However, endothelial cells in human umbilical veins that contain and release NPY and ANP, as well as NO, are inactive locally and it has been suggested that they may have trophic effects on fetal development (Cai et al 1993 a, b ;Salas et al 1995 ;Sexton et al 1995).…”
Section: Long-term Trophic Actions Of Substances Released From Endothmentioning
confidence: 99%